Conditions for the development of next-generation technologies (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2025)
This thesis is aimed at forming students' knowledge in the field of modern mobile communication systems, where leading scientific concepts are presented: mobile communication and the principles of its construction, classification of mobile radio systems, mobile generations, LTE system architecture, requirements for the LTE system. functionality and main components of the system architecture. This course is aimed at forming students' understanding of the principles of organizing radio communications, professional radio communication systems, mobile communication standards and generations. In this thesis, you will acquire the skills of organizing mobile communications. Many communication technologies, duplex channel schemes, organization of handover, development of cellular communication systems. 2.5G generation mobile communication systems, 2.75G generation mobile communication systems, 3G third generation standards, 3.9G or 4G generation standards to instill knowledge and skills in the younger generation.